Joseph J. Schwab's Educational Thought and Its Relevance to the Implementation of the Merdeka Curriculum in Indonesia - Firmansyah Firmansyah (PT. Pusmedia Group Indonesia, 2026)
The development of education policy in Indonesia through the implementation of the Merdeka Curriculum requires a flexible, contextual, and learner-centered curriculum approach. The implementation of this curriculum requires a strong theoretical foundation so that it is not only technical but also reflective. In this context, the ideas of Joseph J. Schwab, particularly his concepts of the practical and the four commonplaces of curriculum, are relevant because they emphasize a deliberative process and contextual curriculum decision-making. Therefore, this study aims to describe Joseph J. Schwab's educational and social background, the main points of Joseph J. Schwab's thinking in the field of education, and analyze the relevance of Schwab's thinking to the implementation of the Merdeka Curriculum in Indonesia. This study is a literature study using a Systematic Literature Review (SLR) approach. Data collection was carried out by gathering various relevant scientific sources identified through online databases, such as Google Scholar, Scopus, and ERIC, using keywords such as: Joseph J. Schwab, curriculum deliberation, The Practical Schwab, Merdeka Curriculum, and Boolean operators (AND, OR, NOT) to broaden or narrow the search for more relevant results. The literature search focused on publications that appeared in the last 15 years (2010–2025). However, several of Schwab's classic works from the 1960s to the 1970s were included because they are the main foundation of his thinking. The data analysis technique was carried out using a thematic synthesis approach. The results of the study show that the concepts of “the practical” and “four commonplaces of curriculum” developed by Schwab are directly related to the principles of the Merdeka Curriculum, particularly in terms of empowering teachers as curriculum designers, student-centered learning, and the integration of social and cultural contexts in the learning process. Schwab also emphasized the importance of a deliberative process in curriculum decision-making, which supports the principles of autonomy and flexibility of educational units in the Merdeka Curriculum. The theoretical implications of this research enrich the study of educational philosophy in Indonesia by offering Schwab as a reflective and contextual alternative foundation. Practically, these findings provide direction for improving the capacity of teachers as context-aware and collaborative learning designers in curriculum design. This study recommends that Schwab's thinking be more widely integrated into teacher training, curriculum development, and national education policy. Thus, the implementation of the Merdeka Curriculum can take place in a more meaningful, democratic, and needs-oriented manner for students.